2020
DOI: 10.1177/0098628320959953
|View full text |Cite
|
Sign up to set email alerts
|

Kindness at First Sight: The Role of Syllabi in Impression Formation

Abstract: Strong faculty–student relationships are an important predictor of student retention and success in higher education. Faculty often work to establish these relationships by developing rapport with students in the classroom, but minimal research has been done on whether syllabus design and language can affect these relationships. The goal of Experiment 1 was to examine whether the use of a more visual syllabus design or more welcoming syllabus language could affect students’ perceptions of their instructors or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…An explanation for the finding is that learner-centered syllabi are more memorable because they are organized and written with an awareness of primacy and recency effects and present information in a friendly and engaging manner (Richmond et al, 2016). While we could demonstrate better memory for the syllabus based on syllabus design, Nusbaum et al (2021) did not. They found that a more visual and more welcoming syllabus only changed perceptions of the instructor and did not change memory for the syllabus content.…”
Section: Syllabus Designmentioning
confidence: 62%
See 1 more Smart Citation
“…An explanation for the finding is that learner-centered syllabi are more memorable because they are organized and written with an awareness of primacy and recency effects and present information in a friendly and engaging manner (Richmond et al, 2016). While we could demonstrate better memory for the syllabus based on syllabus design, Nusbaum et al (2021) did not. They found that a more visual and more welcoming syllabus only changed perceptions of the instructor and did not change memory for the syllabus content.…”
Section: Syllabus Designmentioning
confidence: 62%
“…Drawing from several past studies and the suggestions of scholars regarding learner-centered syllabi (e.g., Gurung & Galardi, 2021, Nusbaum et al, 2021Richmond, 2021;Richmond et al, 2016Richmond et al, , 2019Richmond et al, , 2021, we wrote two new syllabi-one was learner-centered, and the other was instructor-centered. The two syllabi differed in many ways.…”
Section: Methodsmentioning
confidence: 99%
“…Participants reported their impression that the professor is trying to create an inclusive course environment with a single-item (Howansky et al, 2021) on a scale from 0 = not at all true to 100 = very true . Participants reported impressions that the professor is kind, approachable, encouraging, and fair with items adapted from Nusbaum et al (2020) on scales from 1–7, with 1 indicating lacking the trait (e.g., very unkind) and 7 indicating having the trait (e.g., very kind). Participants completed a single-item measure of interest in taking the course on a scale from 1 = not at all interested to 5 = extremely interested , and a single-item measure of the perceived likelihood that the professor was a first-generation student on a scale from 1 = extremely unlikely to 7 = extremely likely .…”
Section: Methodsmentioning
confidence: 99%
“…Syllabi are frequently the first opportunity for instructors to introduce themselves and incorporate ISCs in their teaching. For example, students exposed to visually stimulating syllabi rated the instructor as kinder and more approachable than students exposed to less visual syllabi (Nusbaum et al, 2020). Psychologists have proposed that including diversity statements in syllabi, acknowledging students' diverse identities/backgrounds, and increasing diversity in course materials can improve diversity, equity, and inclusion in psychology courses (Fuentes et al, 2021).…”
mentioning
confidence: 99%
“…Biktimirov and Nilson (2003) implied that graphic syllabi help students to see the course overview. Nusbaum et al (2021) found that students who viewed a visually rich syllabus (as opposed to a less visually rich one) rated the instructor as kinder, more approachable, and more creative. Thus, including graphics on a syllabus would appear to have potential benefits.…”
Section: Visual Images: Graphics or No Graphicsmentioning
confidence: 97%